Implementing integrated services for people with epilepsy in primary care in Ethiopia: a qualitative study - Raquel Catalao; Tigist Eshetu; Ruth Tsigebrhan; Girmay Medhin; Abebaw Fekadu; Charlotte Hanlon (BMC, 2018)
Abstract Background In order to tackle the considerable treatment gap for epilepsy in many low- and middle-income countries (LMICs), a task sharing model is recommended whereby care is integrated into primary health services. However, there are limited data on implementation and impact of such services in LMICs. Our study aimed to explore the perspectives of service users and caregivers on the accessibility, experience and perceived impact of epilepsy treatment received in a task-shared model in a rural district of Ethiopia. Methods A qualitative study was carried out using interviews with purposively sampled service users (n = 13) and caregivers (n = 3) from a community-ascertained cohort of people with epilepsy receiving integrated services in primary care in rural Ethiopia. Interviews followed a topic guide with questions regarding acceptability, satisfaction, barriers to access care, pathways through care and impact of services. Framework analysis was employed to analyse the data. Results Proximity of the new service in local primary health centers decreased the cost of transportation for the majority of service users thus improving access to services. First-hand experience of services was in some cases associated with a willingness to promote the services and inform others of the existence of effective biomedical treatment for epilepsy. However, most service users and their caregivers continued to seek help from traditional healers alongside biomedical care. Most of the care received was focused on medication provision with limited information provided on how to manage their illness and its effects. Caregivers and service users spoke about the high emotional and financial burden of the disease and lack of ongoing practical and emotional support. The majority of participants reported clinical improvement on medication, which in over half of the participants was associated with ability to return to money generating activities. Conclusions Task-sharing improved the accessibility of epilepsy care for services users and caregivers and was perceived as having a positive impact on symptoms and productivity. Nonetheless, promotion of self-management, holistic care and family engagement were highlighted as areas requiring further improvement. Future work on implementing chronic care models in LMIC contexts is warranted.